State and sufism in Iraq: building a "moderate Islam" under Saddam Husayn - Jordan, David (Routledge Sufi series, 2022)
Islam and the Decline of Sufism After the End of the Ottoman Empire -- The Rise of the Baʻth Party and its Early Nationalization of Islam -- Sufis Under the Early Baʻth : First Links to the Regime -- The Religious Propaganda of a Secular Regime -- The New Prominence of Sufi Scholars -- New Opportunities for Sufi Orders -- Sufism to Counter Moral Decay and Wahhabism -- Sufi Ecumenism Against Sectarianism -- The Entanglement of Sufis with the State Elite -- Conclusion -- Afterword : The Naqshbandī Army and the Legacy of the Baʻth Regime's Sufi Revival After 2003